Ecommerce Logistic Finding: Preliminary Work - Al-Imran, G.M.; Mit, Edwin; Junaini, Syarul N. (2015)
Electronic Commerce (EC) Logistics is a buzz word in the present day world economy. Proper delivery of products to the customer in a cost effective way and ensuring customer satisfaction is very much important. This research analyses the ecommerce logistics, makes a discussion on the development of logistics in the EC environment and establish an enhanced algorithm based on road network system, with the aid of the Logistics Information Management System (LIMS). It mainly focuses on faster and cost effective ecommerce logistics distribution.